BATUPASIR â€œBULUKUNINGâ€ PADA LEMPUNG BERSISIK DI DAERAH BANJARNEGARA, JAWA TENGAH ; STUDI PETROLOGI, PROVENAN DAN IMPLIKASI TEKTONIK - Harsolumakso, Agus Handoyo; Puswanto, Eko; Sucipta, IGB Eddy (Bulletin of Geology, 2019)
Sandstone unit in the Bulukuning area, Banjarnegara known and even once proposed as the Bulukuning Formation were formerly referred to as the greywacke sandstones as part of the Luk Ulo Melange Complex which is believed as Early Cretaceous-Paleocene in age. The sandstones are lightly metamorphosed and observed in many places to be inclunded in the exotic blocks within the scaly clay which is generally considered as matrix of melange. This study examines the details of lithological characteristics, their provenances and tectonic implications. Undeformed sequences of the Bulukuning Sandstones represented by well bedded sandstones and siltstones. Determinations of fossil species and association of these sandstones yield Paleo-Nummulites and nanno fossil matrices which strongly suggest Middle-Late Eocene (NP15-16). The highly deformed sequence of Bulukuning Sandstones often show block in matrix characters while others develop more boudinage structures as a result of rigid deformation. Analysis of the scaly clay matrix using the illite crystallinity (IC) value suggested that the deformation controlled the formation of scaly clay and boudinage structures occurred at temperatures around 205.916o - 223.014oC (Â± 30Â°). The provenance study of the sandstones confirms that these are resulted from recycled orogens related to the Micro-Continent collision of East Java with the southeast margin of the Sundaland during the Late Eocene-Early Oligocene period. The collision was subsequently followed by the exhumation of Karangsambung accretion complex, previously formed volcanic rocks and several Sundanese land blocks.